Ionic Surfactants and Aqueous Solutions : Biomolecules, Metals and Nanoparticles - Dumortier Shin, Younok; Dumortier, Remy; Husein, Maen M.; Khoshkbarchi, Mohammad K.; Rabie, Hamid; Rodil R., Eva; Soto, Ana; Vera, Juan H.; Wilczek-Vera, Grazyna (De Gruyter, 2018)
Ionic Surfactants and Aqueous Solutions: Biomolecules, Metals and Nanoparticles covers a wide range of subjects related to aqueous systems, from reverse micelles as ion exchangers to the study of micellar phase transfer catalysis for nucleophilic substitution reactions. The diverse background, expertise and professional interests of the contributors to this book give to it a unique richness of approach in topics of relevance for biotechnology and environmental studies. Over sixty publications presenting research results are combined and expanded in this book by some of the original researchers. At a mature age, and at the summit of successful professional careers, they have taken a second look to the state of the art in the fields that they had pioneered. Eva Rodil and Ana Soto, who had their research formation in the group of Professor Alberto Arce at Universidade de Santiago de Compostela, Spain, are presently professors at that university, Maen Husein is a professor at University of Calgary, Canada. Remy Dumortier, Mohammad Khoshkbarchi, Hamid Rabie and Younok Dumortier Shin, are presently active leaders in the industrial world in Canada and the USA. The editors are retired academics from McGill University, Montreal, Canada, and coauthors of the book Classical Thermodynamics of Fluid Systems.